Book Mavens of Manila : an interpretative phenomenological analysis of contemporary niche publishers in the Philippines - Sagun, Karryl Kim Abella (Nanyang Technological University, 2019)
This thesis documents and analyzes the experiences of niche publishers in the Philippines. Chapter One elaborates on my objectives and the structure of the thesis. Chapter Two provides a general overview of book history, while Chapter Three offers literature on the Philippine book trade. Chapter Four presents my qualitative, phenomenological method. Chapter Five, the first study, focuses on university publishers. It was through this study that I found that roles in Darnton’s circuit are not mutually exclusive. Chapter Six, the second study, examines the Philippine book trade from the perspective of comics publishers. Findings reinforce the overlapping roles in the circuit, while adding another actor (distributor). Chapter Seven, the third study, probes the experiences of self-publishers. Here I found that not all authors are created equal—some are able to self-publish both in print and electronically, some just online, while some are still controlled by a traditional publisher. The fourth and final study, Chapter Eight, investigates children’s publishers. My findings demonstrate that Darnton’s claim that the external forces influencing the life cycle of the book comprise a single entity is flawed. The last chapter, Chapter Nine, provides a summary of my work and its contributions, a discussion on its limitations, and suggestions for future research.